1960
DOI: 10.1530/jrf.0.0010249
|View full text |Cite
|
Sign up to set email alerts
|

An Autoradiographic Method for the Study of Egg Transport in the Rabbit Fallopian Tube

Abstract: A new technique is described in which 120-µ anionic resin spheres, impregnated with the radioactive gold isotope 198Au, are employed to simulate rabbit eggs. By their use, a study has been made of the pattern of egg transport in the Fallopian tube of the rabbit in vivo. (2) It has been shown that, in the first 8 hr after ovulation, the spheres have travelled 49% of the length of the tube. During the next 40 hr, movement down the tube is very slow until, at 48 hr after ovulation, the spheres are concentrated ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

1965
1965
1988
1988

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 7 publications
4
37
0
Order By: Relevance
“…As the ovum proceeds toward the uterine end of the tube, the relative probability of a contraction occurring on the ampullary side of the ovum increases. One would therefore expect the mean ovum velocity to increase with position along the tube, a hypothesis in agreement with the mean velo city curves of H arper et al [17]. Only contractions near an ovum are effective in developing sufficient pressure gradients across the ovum to overcome the forces resistive to motion.…”
Section: Formulation Of a Modelsupporting
confidence: 80%
See 1 more Smart Citation
“…As the ovum proceeds toward the uterine end of the tube, the relative probability of a contraction occurring on the ampullary side of the ovum increases. One would therefore expect the mean ovum velocity to increase with position along the tube, a hypothesis in agreement with the mean velo city curves of H arper et al [17]. Only contractions near an ovum are effective in developing sufficient pressure gradients across the ovum to overcome the forces resistive to motion.…”
Section: Formulation Of a Modelsupporting
confidence: 80%
“…However, although the mech anism is complex and contains a highly random component, variability in average transport rates is surprisingly small between different ova in the same oviduct, between rates in the left and right oviducts in the same animal and between groups of animals in similar states. The coefficient of variation (3) of the measured distance from the fimbrial end of the tube at a given time after ovulation in the rabbit is on the order of 30% [17,22], This relative ly small variability suggests a well-defined system rather than a collection of random events. The position-time curve, however, does not reflect oscillatory motion and is therefore a smoothed out average representation even if all ova were to travel identically.…”
Section: Formulation Of a Modelmentioning
confidence: 99%
“…Following the original work of Harper et al (1960) the transfer of microspheres to the oviduct for studying their transport to the uterus as surrogate ova has been accomplished mostly in the rabbit. Pauerstein et al (1975) showed that surgical transfer changes the transport of native eggs.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods has been used to observe movements of the Fallopian tube and their effect on sperm and ovum transport, for example, direct ob¬ servation of the tubes (Westman, 1926), utero-tubal insufflation (Bonnet, 1964), passage of radiopaque materials (Bjork, 1959) and the passage of natural ova (Wintenberger, 1953;Greenwald, 1961) and artificial ova (Harper, Bennett, Boursnell & Rowson, 1960).…”
Section: Introductionmentioning
confidence: 99%